2014
DOI: 10.23986/afsci.41385
|View full text |Cite
|
Sign up to set email alerts
|

Intercropped red beet and radish with green bean affected microbial communities and nodulation by indigenous rhizobia

Abstract: The impact of intercropping green bean (Phaseolus vulgaris L.) with red beet (Beta vulgaris L. var. rubra) and radish (Raphanus sativus L.), two non-legume plants, on the plants' yields, as well as the effect on occurrence and enumeration of microorganisms in the rhizosphere was studied. The intercrop efficacy evaluation, using Land equivalent ratio, revealed values above 1.0 for all intercropped treatments. Diversity of rhizobia from green bean nodules under different intercropping and fertilizing conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Unlike for beetroot, intercropped radish yielded significantly better than as a sole crop. This confirmed the results of our previous research on intercropping other varieties of green beans and radish, where we found significantly lower intercrop efficiency in green beans, and higher in radish (Ugrinovic et al, 2014). The differences in intercrop efficiency imply radish as a strong competitor and dominant species in intercrop system which includes species from Fabaceae family.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Unlike for beetroot, intercropped radish yielded significantly better than as a sole crop. This confirmed the results of our previous research on intercropping other varieties of green beans and radish, where we found significantly lower intercrop efficiency in green beans, and higher in radish (Ugrinovic et al, 2014). The differences in intercrop efficiency imply radish as a strong competitor and dominant species in intercrop system which includes species from Fabaceae family.…”
Section: Resultssupporting
confidence: 91%
“…Plant growth promoters, such as beneficial strains of some bacterial species {Azptobacter sp, Derxia sp., Bacillus sp., Rhizobium heguminosarum etc. ), contribute to the plant growth and reduce the need for additional fertilization, which refers to both organic and conventional production (Hayat et al, 2010;Sripontan et al, 2014;Ugrinovic et al 2014;Miskoska -Milevska et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al (2019) and Cerecetto et al (2021) conducted research on the effects of continuous tillage of beet crops on the soil microbial community, and their results showed that conventional tillage practices reduced some aspects of microbial diversity compared with no till practices, in agreement with our findings. However, a limitation of our study is that we considered only one crop (beet) although research (Lange et al, 2015; Ugrinovic et al, 2014) shows that different crops influence soil properties, microbial structure and diversity in different ways. Further studies are therefore needed to determine the influence of different crops on soil microbial diversity.…”
Section: Discussionmentioning
confidence: 99%